Transferrin-conjugated nanoparticles of Poly(lactide)-d-α-Tocopheryl polyethylene glycol succinate diblock copolymer for targeted drug delivery across the blood-brain barrier - Gan, C.W. (2014)
10.1016/j.biomaterials.2010.06.053